Legitimasi Resolusi Dewan Keamanan PBB dalam Konflik di Darfur Sudan - Darnela, Lindra (UIN Sunan Kalijaga, 2012)
Massive demonstrations in several Arab countries lead to a civil war among the citizens. This is of special concern to the United Nations as the global nature of international organizations to participate in the intervention of the conflict accompanied by making resolutions. These cases are suing back the legitimacy of international law, especially international organizations like the UN. In this study describes about the legitimacy of the UN Security Council resolutions, and thenapply it to analyze the conflict in Darfur. The UN is an international organization which is the subject of public international law, so that the resulting public policy becomes legally binding for member states based on the collective legitimation. In the application of collective legitimation is in practice often does not correspond to the value of morality and even a lot of opposition as in the case of the conflict in Darfur whose governments openly reject the contents of the resolution issued by the United Nations.